2016
DOI: 10.1097/hcr.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Role of Exercise Testing in Contemporary Cardiac Rehabilitation

Abstract: Symptom-limited (maximal) exercise testing before cardiac rehabilitation (CR) was once an unambiguous standard of care. In particular, it served as an important screen for residual ischemia and instability before initiating a progressive exercise training regimen. However, improved revascularization and therapy for coronary heart disease has led many clinicians to downplay this application of exercise testing, especially because such testing is also a potential encumbrance to CR enrollment (delaying ease and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 74 publications
0
29
0
3
Order By: Relevance
“…Several randomized trials have verified that aerobic exercise (AE) produced possibly the greatest improvements in peak oxygen consumption (Vo 2 ) and left ventricular ejection fraction [8]. Furthermore, after systematically analyzing studies on exercise-based CR, Taylor et al [9,10] found that CR could decrease total mortality by 20% and cardiac mortality by 30%, and could decrease cardiovascular risk factors. Currently, AE-based CR is a class I recommendation for increasing survival in many guidelines for patients with ASCVD, whether acute cardiac syndrome or stable angina pectoris [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized trials have verified that aerobic exercise (AE) produced possibly the greatest improvements in peak oxygen consumption (Vo 2 ) and left ventricular ejection fraction [8]. Furthermore, after systematically analyzing studies on exercise-based CR, Taylor et al [9,10] found that CR could decrease total mortality by 20% and cardiac mortality by 30%, and could decrease cardiovascular risk factors. Currently, AE-based CR is a class I recommendation for increasing survival in many guidelines for patients with ASCVD, whether acute cardiac syndrome or stable angina pectoris [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPET) presumes that a patient has requisite capacities of strength and balance that in many cases are too limited for CRF testing. Therefore, a broader range of physical function assessments is an important goal . Ideally, functional assessments for older adults need to gauge a wide range of capacities in this heterogeneous population, with prognostic sensitivity, and capacity to track changes over time (ie, sufficiently sensitive to delineate decrements or improvements).…”
Section: Functional Assessmentmentioning
confidence: 99%
“…Cardiorespiratory fitness (CRF) is a powerful indicator of morbidity and mortality. It is best measured using graded symptom‐limited CPET and directly quantified as peak oxygen uptake (VO 2 ) . Although standard exercise testing can be used to estimate metabolic equivalents (METs) a metabolic index conceptually related to peak VO 2 , METs are calculated and are relatively less precise than VO 2 assessments.…”
Section: Functional Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently reported case, the BrS ECG pattern was likely induced by ischemia (Brugada phenocopy) [34]. ExT and cardiopulmonary exercise testing may provide information on exercise safety and may reveal or augment the BrS ECG pattern [29,35,36]. The specific role of these tests in the management of BrS patients requires further studies.…”
Section: Risk Assessment In Brugada Syndromementioning
confidence: 99%